2021
DOI: 10.3390/ijerph18052434
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Healthcare Workers amid the COVID-19 Pandemic: A Japanese Cross-Sectional Survey

Abstract: The coronavirus disease 2019 (COVID-19) global pandemic has drastically changed how we live and work. Amid the prolonged pandemic, burnout of the frontline healthcare professionals has become a significant concern. We conducted a cross-sectional survey study to provide data about the relationship between the COVID-19 pandemic and the prevalence of burnout in healthcare professionals in Japan. Healthcare workers in a single Japanese national university hospital participated in the survey, including basic demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 29 publications
(45 reference statements)
12
72
0
3
Order By: Relevance
“…A substantial number of the articles explored in detail how HCWs, patients, and the general community faced challenges such as burnout in particular, as well as explored suitable coping measures. This is consistent with the articles published overseas, which also found significant burnout amongst healthcare workers [504][505][506][507] and adverse psychological effects on the rest of the community [508][509][510][511]. The articles published locally have detailed various responses to this situation, such as a digital MyCare application [417], a psychological preparedness kit for HCWs [409], and peer support services [430], which demonstrate that our community has been able to anticipate and react quickly to the psychological impact of this pandemic.…”
Section: Psychological Impactsupporting
confidence: 82%
“…A substantial number of the articles explored in detail how HCWs, patients, and the general community faced challenges such as burnout in particular, as well as explored suitable coping measures. This is consistent with the articles published overseas, which also found significant burnout amongst healthcare workers [504][505][506][507] and adverse psychological effects on the rest of the community [508][509][510][511]. The articles published locally have detailed various responses to this situation, such as a digital MyCare application [417], a psychological preparedness kit for HCWs [409], and peer support services [430], which demonstrate that our community has been able to anticipate and react quickly to the psychological impact of this pandemic.…”
Section: Psychological Impactsupporting
confidence: 82%
“…Participants included physicians, nurses, pharmacists, clinical engineers, and physical therapists in Okayama University Hospital (OUH; a tertiary-care Japanese national university hospital with more than 800 beds). Before the initial cross-sectional study that we previously reported [ 8 ], we conducted a power analysis for two proportions to estimate a sample size required to detect the significant differences between the prevalence of burnout among those engaged in the COVID-19 patient care in the past 2 weeks compared to those who did not. We defined the prevalence of burnout in those who engaged in COVID-19 care in the period as 70% and those who did not as 20% in the analysis based on the previous studies [ 12 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…While burnout syndrome is not included in the list of mental disorders in the 10th revision of the International Classification of Diseases, a study suggested its association with major mental disorders such as insomnia, depression, anxiety, and post-traumatic symptoms [ 7 ]. We previously reported that HCWs who engaged in care of COVID-19 patients had significantly higher burnout rates (50.0%) than those who did not, and those working in the intensive care unit were more likely to have experienced burnout than those in floors [ 8 ]. The study was done amid the third surge of the COVID-19 cases in Japan in November 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is consistent across diverse settings that healthcare professionals in intensive care settings have been at higher risk during the pandemic compared to other healthcare settings. [106][107][108][109][110] Working in a COVID-19 unit or hospital or in an emergency department has also been associated with elevated burnout. 108,111,112 During the pandemic, higher levels of burnout have consistently been reported in nurses than in other hospital-based healthcare professionals in Canada and internationally.…”
Section: Nurses and Workers In Intensive Care And Emergency Department Settings Are At Higher Risk Of Burnoutmentioning
confidence: 99%